Managing end-user participation for the adoption of digital livestock technologies: expectations, performance, relationships, and support - Schillings, J.; Bennett, R.; Rose, David Christian (Taylor & Francis, 2023)
Purpose: End-user participation is often encouraged to promote the uptake of Digital Livestock Technologies (DLTs). However, managing participation during DLT development can be challenging. We explore how participation decisions can impact end-users’ engagement and attitudes towards the process, before suggesting strategies for improved management of the participation process. Methodology: We explored the experiences of end-users (e.g. farmers and farm assessors) and other stakeholders (e.g. developers, researchers, industry) involved in the development and testing of DLTs on UK farms, using semi-structured, in-depth interviews (N= 31). Findings: Participation can help develop technologies that better align with users’ needs, promote learning, and encourage feelings of ownership. However, participation can be a double-edged sword. Inadequate levels of involvement, management of stakeholder relationships and expectations, and available support can negatively impact end-users’ engagement and attitudes. Practical implications: Our study highlights the importance of understanding how management decisions during the participatory development of DLTs can influence the engagement and attitudes of end-users towards the process. Theoretical implications: The study contributes to the participation literature in agriculture and demonstrates the importance of using a critical lens to avoid making normative assumptions that participation necessarily promotes uptake in a linear, uncomplicated fashion. Originality/Value: Participation is seen as key for technology adoption. However, the potential downsides of participation have received less attention in relation to the engagement of end-users in the process.
Keywords: Digital Livestock Technologies; Participation; Precision Livestock Farming; Stakeholder engagement; Technology adoption; Livestock monitoring